Regulatory mechanisms of muscle fiber types and their possible interactions with external nutritional stimuli - Koichi Nakazato; Arata Tsutaki (Japanese Society of Physical Fitness and Sports Medicine, 2012)
In this review, we briefly summarize muscle fiber types and mechanisms that regulate their expression from nutritional stimulus. To begin with, we introduce genes and their location on myosin heavy chains (MyHC). Next, we show three major transcriptional controls for MyHCs as (1) calcium signaling, (2) AMPK signaling, and (3) miRNA/anti-sense RNA regulations. Following this, we summarize possible nutrients that effect muscle fiber type transformation. The possible contributors are caloric restriction, polyphenols, and high-fat and high-protein diets. We think that nutritional intervention will be a useful way to control muscle fiber type switching. This approach could be adopted by athletes as a means to condition their muscles.